2016
DOI: 10.1177/2158244016674762
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Students in Recovery on a Rural College Campus

Abstract: In response to this challenge, Collegiate Recovery Programs (CRPs) have evolved to provide campus-based support services to college students in recovery. The first CRP was established at Brown University in 1977, and more than 100 higher education institutions and recovery high schools now offer some level of recovery support (Finch & Karakos, 2014). Roughly, two to five new CRP programs emerge each year (Laudet & Humphreys, 2013). CRPs currently vary in the services they offer, but a comprehensive CRP incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Nationwide, there were roughly 58 programs that served 1,354 students in Fall 2014 (Transforming Youth Recovery, ). The current sample represented a portion of the overall population of students in recovery pursuing higher education, and the sample size was consistent with previous research (Cleveland et al, ; Scott et al, ).…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…Nationwide, there were roughly 58 programs that served 1,354 students in Fall 2014 (Transforming Youth Recovery, ). The current sample represented a portion of the overall population of students in recovery pursuing higher education, and the sample size was consistent with previous research (Cleveland et al, ; Scott et al, ).…”
Section: Methodssupporting
confidence: 83%
“…Stigma is a primary issue facing individuals in recovery who are pursuing postsecondary education (Dearing, Stuewig, & Tangney, ), yet it has been understudied in recent years (Scott, Anderson, Harper, & Alfonso, ). Such stigma is societally pervasive and is prevalent within the collegiate environment (Dearing et al, ; Perron et al, ).…”
Section: Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…In a national survey, SAMSHA (2016) reported that 1 in 6 young adults between the ages of 18-24 met criteria for a substance use disorder and were considered to be in need of treatment. Of those, only 7.2% received specialized care, and 92.8% received no formal treatment (Park-Lee, Lipari, Hedden, Kroutil, & Porter, 2017). A number of studies have examined the unique challenges posed by high-risk collegiate environments and the essential role that peer-to-peer networks and social supports play in supporting the needs of students in recovery (Botzet, Winters, Fahnhorst, 2008;Cleveland, Harris, & Wiebe, 2010).…”
Section: Purpose and Scopementioning
confidence: 99%
“…By providing resources and structural support for students (e.g., academic advising, safe spaces, 12-step meetings for those who need them), CRPs position students in recovery to be more successful academically, and to stay well in their recovery (Cleveland et al, 2007; Patterson et al, 2021). CRPs oftentimes serve as a student's primary place for social interaction and identity (Bell et al, 2009; Scott et al, 2016), which might be an asset for survivors of sexual assault dealing with substance use.…”
Section: Discussionmentioning
confidence: 99%